High pressure liquid chromatographic analysis of in vivo metabolites of N-(substituted phenyl)-N '-(1,3,5trimethyl pyrazole-4-yl)thioureas in rats - (:unkn) unknown (SPRINGER FRANCE, 2007)
The aim of this study was to investigate the in vivo metabolism of N-(substituted phenyl)-N' -(1,3,5-trimethylpyrazole-4-yl)thioureas (substrate) as model compounds in rats via HPLC. The substrates, N-(4-fluoro/chlorophenyl)-N'(1,3,5-trimethylpyrazole-4yl)thioureas (T2 and T3), and their possible metabolites were synthesized and the structures of the compounds were elucidated both by spectral and elemental analysis. Substrates were dissolved in 5% gum arabic and administered 100 mg/kg intraperitoneally (i.p.) in a volume of 0.1 ml/100 g. Blood samples were withdrawn before and at 30 min, 1, 2, 4, 8, 12 and 24 h post-dose. Chromatographic separation of the substrate and its metabolites was performed using a Hichrom chromasil C-18 column (150 mmx4.6 mm i.d., 5 mu m particle size). The optimal composition of the mobile phase was achieved by using different mixtures of pure methanol and water. From the biotransformation of these thiourea compounds, N-dealkylation metabolites N-(4-fluoro/chloro-phenyl)-N'-(3,5-dimethylpyrazole-4-yl)thioureas (T1 and T4) were identified together with unchanged substrate (T2 and T3) in the plasma by comparing them to reference standards via HPLC UV/DAD.
Keywords: pyrazoles; thioureas; in vivo metabolism; HPLC; THIOUREA; VITRO; IDENTIFICATION; INHIBITORS